The Role of Educators in the Formation of Students' Leadership Character in the Leadership Material of Khulafaur Rasyidin: Peran Pendidik dalam Pembentukan Karakter Kepemimpinan Peserta Didik Pada Materi Kepemimpinan Khulafaur Rasyidin - Dikriati Kamalasari; Martin Kustati; Rezki Amelia; Gusmirawati Gusmirawati (Indonesian Journal of Innovation Multidisipliner Research, 2024)
This study aims to find out the role of educators in implementing leadership characters in the subject of Islamic Cultural History in grade VII MTsN 7 Agam in the material of Khulafaur Rasyidin Leadership.  This type of research is qualitative research with the subject of this research being Islamic Cultural History educators and students of grade VII MTsN 7 Agam. The data collection techniques used are observation, interviews and documentation. Then this study uses data analysis through data reduction, data display, and conclusion drawn. The results of this study show that the role of educators is as partners, resource persons, and companions. Educators play the role of partners, namely cooperation between educators and other educators, parents or other parties who are tasked with paying attention to the development of students. Educators act as resource persons tasked with providing information to students about many things related to learning and so on. Meanwhile, educators as companions are in charge of providing direction and advice related to the field or discussion being pursued.